Comparative analysis of standard and contrast elastic resistance band training effects on physical fitness in female adolescent handball players - Hammami, M.; Zmijewski, P. (Biology of Sport, 2024)
This study aimed to compare the effects of two elastic band 10-week training programmes on the athletic performance in adolescent female handball players. Participants aged 16.0 ± 0.5 years were randomly assigned to control (CNT, n = 12), standard elastic band (SEB, n = 12), or contrast elastic band (CEB, n = 12) programmes, each performed twice a week supplementing the regular training. The sprint (10 m and 20 m), modified Illinois change-of-direction test (COD), squat jump (SJ), countermovement jump (CMJ), standing long jump (SLJ), back extensor strength (BES), medicine ball throw (MBT), 1-RM bench press, 1-RM half squat, repeated sprint ability, and force-velocity (F-V) tests were measured before and after the intervention. Both CEB and SEB similarly improved sprint (p < 0.01 and p < 0.01) and COD (p < 0.001 and p < 0.01) when compared to CNT. Jumping performance improved significantly (SJ p < 0.01; CMJ p < 0.05) only in CEB, compared to CNT. Strength improved in both experimental groups (p < 0.01; ES: 0.73 < d < 1.59) compared to CNT, and there was a greater increase for CEB than SEB (p < 0.05) in the medicine ball throw (Table 3). Both CEB and SEB increased all RSA scores compared to CNT (p < 0.01; ES: 0.10 < d < 1.22), without significant difference between them. All F-V scores increased significantly in CEB and SEB compared to CNT (p < 0.01; ES: 0.45 < d < 2.47). In addition, CEB showed substantial gains in performance for PPabs, PPrel, and F0 (p < 0.001, p < 0.001 and p < 0.05, respectively) compared to SEB. Ten-week elastic band training conducted within the competitive season improved limb strength, power and F-V profile in female handball players, with a superior effect of the contrast elastic band training mode for upper-limb strength and F-V characteristics.